Attitudes of Local Population on the Importance of Events Nourishing Culture and Tradition of Croats in Vojvodina - Pivac, Tatjana; Blešić, Ivana; Besermenji, Snežana; Gavrilović, Darko (Turizam, 2020)
AP Vojvodina is a highly multi-ethnic community, with 29 nations and national or ethnic groups living on its territory. Croats make only 2.43% of the population of Vojvodina, but with their rich culture and tradition, they represent a significant potential for the development of Vojvodina's cultural tourism. The richness of customs is best represented through numerous events that take place in areas with the majority of Croatian population. The paper presents the results of a survey conducted to determine how informed the population of Vojvodina is about the maintenance and significance of events of Croats in Vojvodina. A sample of 158 respondents was obtained. Descriptive statistical analysis, t-test of independent samples and analysis of variance ANOVA were used to analyse the obtained data.